2018
DOI: 10.21597/jist.427894
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Conservation Agriculture for Turkey

Abstract: Conservation agriculture (CA) is concerned with profitableness and sustainability by optimizing agricultural procedures while conserving input and minimizing any impact on natural resources. Technologies that benefit the environment can often have negative effect on crop productivity and offer short-term profitability. CA is one of few practices that can enhance yield, economic returns, and food security while conserving the natural resources. The principles of the CA are zero-tillage, permanent soil cover and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Gozubuyuk et al [42] observed that straw cover reduced operational fuel consumption, which corroborates this research; the authors obtained liters per hour fuel savings of 3.5-fold compared to areas without vegetation cover. Conservation tillage practices, especially no-till practices, generally reduce fuel consumption, compared to conventional tillage [43].…”
Section: Resultsmentioning
confidence: 99%
“…Gozubuyuk et al [42] observed that straw cover reduced operational fuel consumption, which corroborates this research; the authors obtained liters per hour fuel savings of 3.5-fold compared to areas without vegetation cover. Conservation tillage practices, especially no-till practices, generally reduce fuel consumption, compared to conventional tillage [43].…”
Section: Resultsmentioning
confidence: 99%